International trade and retailing: Diversity versus accessibility and the creation of retail deserts - Carsten Eckel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2007)
The retail sectors in many industrialized countries have experienced a large increase in concentration and the appearance of so-called etail deserts areas of low retail provision. This study addresses the role of international trade in this process. The analysis shows that by raising product diversity, international trade also raises the costs of provision in retailing and leads to a consolidation in this industry. As a consequence, surviving retailers have larger catchment areas and consumers have to travel longer distances for their errands. These adjustments in retailing create a trade-off between diversity and accessibility, and international trade is not unambiguously welfare improving.
Keywords: F12; L11; L81; 330; international trade; retailing; diversity; accessibility; retail deserts; Einzelhandel; Versorgung; Internationaler Wettbewerb; Produktdifferenzierung; Wirtschaftskonzentration; Einzelhandelsstandort; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie